Antibacterial potentials of Rothmannia octomera (Rubiaceae) root extracts on a few bacterial etiologies of respiratory tract infections: Antibacterial potentials of Rothmannia octomera extracts on respiratory bacteria - Sipowo Tala, Viviane Raïssa; Tchio Mokem, Sandrine; Tene Tcheghebe, Olivier; Fotsing Kwetche, Pierre René; Tchokonte-Nana, Venant (Iranian Journal of Pharmaceutical Sciences, 2026)
Rothmannia octomera is a plant of the Rubiaceae family used in traditional medicine to treat bronchopulmonary infections. To contribute to the valorization initiatives of this plant, we undertook a study of its root phytochemistry. We assessed its antibacterial potential against Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus, which are considered bacterial etiologies of respiratory infections. The phytochemical screening of the hydroethanolic (30:70 v/v) and CH2Cl2/MeOH (50:50 v/v) extracts of Rothmannia octomera, obtained by maceration, was carried out using colorimetric and precipitation tests for several groups of secondary metabolites. For the antibacterial potential of the extracts, minimal inhibitory and bactericidal concentrations (MICs and MBCs) were determined by macrodilution in a liquid medium. Results revealed the presence of phenols, tannins, flavonoids, sterols, anthraquinones, and saponins in both extracts. MIC values for the hydroethanolic extract ranged from 12.5 to 200 mg/mL, while MBC values varied from 50 to 400 mg/mL. For the CH2Cl2/MeOH extract, the MIC values recorded ranged from 50 to 200 mg/mL, and the related BMCs ranged from 100 to 200 mg/mL. The BMCs/MICs ratios revealed a bactericidal effect of the hydroethanolic extract on Pseudomonas aeruginosa and Klebsiella pneumoniae, as well as a bacteriostatic potential on Staphylococcus aureus. With the CH2Cl2/MeOH extract, bactericidal action was observed against all the bacteria tested. This study justifies, for the first time, at least in part, the use of Rothmannia octomera in traditional medicine. Indeed, investigations on the safety of this plant and dosages required for its optimal use in disease control are necessary.